Biosensors for Monitoring Airborne Pathogens. (August 2015) - Fronczek, Christopher F.; Yoon, Jeong-Yeol
Airborne pathogens affect both humans and animals and are often highly and rapidly transmittable. Many problematic airborne pathogens, both viral (influenza A/H1N1, Rubella, and avian influenza/H5N1) and bacterial ( Mycobacterium tuberculosis, Streptococcus pneumoniae, and Bacillus anthracis ), have huge impacts on health care and agricultural applications, and can potentially be used as bioterrorism agents. Many different laboratory-based methods have been introduced and are currently being used. However, such detection is generally limited by sample collection, including nasal swabs and blood analysis. Direct identification from air (specifically, aerosol samples) would be ideal, but such detection has not been very successful due to the difficulty in sample collection and the extremely low pathogen concentration found in aerosol samples. In this review, we will discuss the portable biosensors and/or micro total analysis systems (µTAS) that can be used for monitoring such airborne pathogens, similar to smoke detectors. Current laboratory-based methods will be reviewed, and possible solutions to convert these lab-based methods into µTAS biosensors will be discussed.